2015
DOI: 10.1016/j.mad.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

MARK-AGE biomarkers of ageing

Abstract: Many candidate biomarkers of human ageing have been proposed in the scientific literature but in all cases their variability in cross-sectional studies is considerable, and therefore no single measurement has proven to serve a useful marker to determine, on its own, biological age. A plausible reason for this is the intrinsic multi-causal and multi-system nature of the ageing process. The recently completed MARK-AGE study was a large-scale integrated project supported by the European Commission. The major aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 86 publications
1
140
0
5
Order By: Relevance
“…Recent studies have suggested that a big cohort of parameters is needed in order to accurately estimate the biological age [37]. The present study demonstrates that the five immune functions analyzed are valid enough to be used as indicators of an individual's health and remaining lifespan and therefore, are proposed as markers of biological age.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have suggested that a big cohort of parameters is needed in order to accurately estimate the biological age [37]. The present study demonstrates that the five immune functions analyzed are valid enough to be used as indicators of an individual's health and remaining lifespan and therefore, are proposed as markers of biological age.…”
Section: Discussionmentioning
confidence: 57%
“…The recruitment of the participants and the collection of anthropometric markers (weight, height), medical history (interviewed by trained field workers), and lifestyle characteristics took place between November 2008 and June 2012 at the following centers: Hall in Tirol and Innsbruck (Austria), Namur (Belgium), Esslingen (Germany), Athens and nearby regions (Greece), Bologna (Italy), Warsaw (Poland), and Tampere (Finland). Publications describing the project design, study population, and standard operating procedures have been recently published [20,21,22]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, most studies have been carried out in the United States and few in Europe, but it is known that dietary habits differ strongly between these continents/regions. Therefore we measured plasma carotenoids, tocopherols, and retinol in healthy participants aged 35–74 years as part of the MARK-AGE study, a large-scale European multicenter study aiming to identify biomarkers of age and healthy aging [20]. The main objective of the present study was to elucidate the role of age, other demographic characteristics, and dietary habits on the plasma concentrations of carotenoids, tocopherols, and retinol in a large age-stratified group recruited from the general European population.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of biomarkers studied to date include Interleukin-6, tissue necrosis factor ␣, growth hormone, and testosterone (Simm et al, 2008). However, none of these have proven effective in measuring biological age on its own (Bürkle et al, 2015). One of the most studied biomarkers of ageing is telomere length (nucleoprotein structures at the ends of chromosomes), since telomere length decreases as age increases.…”
Section: Biological Agementioning
confidence: 99%
“…The use of a combination of biomarkers to measure biological age is also gaining interest in ageing research. In MARK-AGE study, a set of biomarkers of ageing was identified to calculate biological age (Bürkle et al, 2015). Many computational algorithms are also available to calculate biological age based on bio-markers, for example Klemera Doubal's method (Klemera and Doubal, 2006).…”
Section: Biological Agementioning
confidence: 99%